Experimental Study on the Evolution of Single-Mode Interface Induced by Co-Directional Rarefaction and Shock Waves - Xing GAO; Xu GUO; Zhigang ZHAI; Xisheng LUO (气体物理)
Developments of a single-mode light/heavy interface accelerated by co-directional rarefaction and shock waves were investigated. Induced by the rarefaction waves, the light/heavy perturbation amplitude experiences an oscillatory growth, which is referred to as the Rayleigh-Taylor (RT) stability. Based on the one-dimensional theory on interface movement induced by rarefaction waves, the classical RT stability model was modified by additionally considering the variations of acceleration and density. The modified model can well predict the oscillatory growth behavior of the perturbation amplitude. In addition, the amplitude growth after the shock impact at different moments was studied. It was found that it is feasible to manipulate the perturbation growth through the shock impact, depending upon the sign of vorticity deposited by the rarefaction waves and shock waves. Moreover, the interface evolution after the shock impact changes from the RT stable state to the Richmyer-Meshkov (RM) unstable state, which is different from the situation when the perturbation is accelerated by counter-directional rarefaction and shock waves, in which the RT behavior will be kept after the shock impact. In the present work, the linear and nonlinear growth rates after the shock impact can respectively be predicted by the linear superimposition principle and classical nonlinear model.